La incidencia del correcto uso de los pictogramas en la lectoescritura en niños de 4 años de edad del centro de desarrollo infantil los conejitos ubicado al sur de la ciudad de Guayaquil. - Tovar Gómez, Evelyn Katherine (2016)
This project is based on research on the influence of the correct use of pictograms in reading and writing the initial level II, because it has been observed that the level of pre-school are not using the educational resources necessary to take advantage develop and strengthen the skills and abilities that at this early age can be exploited in this case reading skills and writers. At this level the children are in a critical and appropriate period in which they stored easily skills, knowledge, skills, values, principles and others……